A Study on the Effect of Housing on Growth Performance of Nellore Lambs (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect of housing on growth performance of Nellore Jodipi  lambs under tropical environmental conditions. Thirty weaned Nellore ram lambs of 3-4 months age were selected based on body weight (average initial body weight) and randomly divided into three  groups of ten animals each. The lambs in Group-I were housed with morum flooring and asbestos  roofing with tree shade, while Group-II lambs were housed with morum flooring and asbestos roofing  without tree shade and Group-III lambs were housed with elevated slatted flooring and galvalume  roofing without tree shade. Temperature and humidity values were significantly (P
Keywords: Nellore Jodipi lambs; housing; tree shade; elevated slatted flooring; heat stress